Prevalence of occupational injuries and associated factors among solid waste collectors in Jigjiga city, eastern Ethiopia: a cross-sectional study design - Abib, Muktar; Tolera, Sina Temesgen; Hashi, Abdiwahab; Mulugeta, Yohannes; Temesgen, Liku Muche (Frontiers in Epidemiology, 2024)
Background: Solid waste collectors play an important role in maintaining health and hygiene in cities globally. The risk levels are very high in low-income countries since solid waste collectors have low socio-economic status and are exposed directly, unknowingly, and without adequate personal protection to municipal solid waste that contains hazardous materials. Solid waste collectors in Ethiopia are at high risk of occupational injuries due to the manual collection of hazardous solid waste by hand. In Jigjiga city, so far, there has been no study or published research showing the prevalence of occupational injuries and associated factors among municipal solid waste collectors.Objective: To assess the prevalence of occupational injuries and associated factors among solid waste collectors in Jigjiga City, Somali Regional State, Ethiopia, 2023.Methods: An institutional cross-sectional study was conducted in Jigjiga City, Somali Regional State, involving 247 solid waste collectors. Data was collected through an observational and structured questionnaire and analyzed using Epi Info and STATA software programs. The study used systematic random sampling techniques and bivariate and multivariable logistic regression analyses to determine the statistical association between the outcome variable and independent variables. The significance of the association was tested using the 95% confidence interval and p value (< 0.05).The overall prevalence of occupational injuries was 54.7% (95% CI: 48.2%, 60.6%).Training on health and safety measures before employment [AOR: 0.43, 95% CI (0.24, 0.80)],sleeping problems [AOR: 3.28, 95% CI (1.86, 5.78)] and Temporary workers [AOR: 2.14, 95% CI (1.16, 3.95)] were significantly associated with occupational injuries.The prevalence rate of occupational injuries among solid waste collectors in Jigjiga City was high. There should be preventive measures, like giving Training on Health and safety before employment, to safeguard the health and safety conditions of the workers.